The world of pumpkins - G. A. Khimich; V. P. Kushnereva (Овощи России)
Genus Cucurbita includes about 30 species. In Russia the genus is mostly presented by 3 following species: winter squash (Cucurbita maxima Duch); acum squash (Cucurbita pero), they include marrow, Pattypan squash; butternut squash (Cucurbita moschata Duch).The research group of the institute has bred cultivars of pumpkin, marrow type and Pattypan squash with high yield and cold resistant abilities, resistant to pathogens. All these cultivars meet all high requirements of the market. With the use of all offered cultivars it has become possible to grow them one by another like a conveyer during a vegetative period in Moscow region.